Leadership Style of School Principals in Improving Teacher Professional Competence in Kuta Alam Sub-District, Banda Aceh - Yusuf, Idawani; Harun, Cut Zahri; Usman, Nasir (FKIP Universitas Lampung, 2021)
Abstract: The purpose of the study was to investigate the leadership style of school principals in improving teacher professional competencies. This study uses a qualitative approach with descriptive methods. Data collection is done through interviews, observation, and documentation studies. The research subjects were principals, vice principals, teachers and supervisors in elementary schools in Gugus Melati, Kuta Alam Subdistrict, Banda Aceh City. The results of the study were found: (1) Principal Leadership Style in improving elementary teacher professional competencies, namely in a participatory (participating) style, the principal also implements an instructional style in improving teacher discipline, and applies a consultative style (selling) in increasing teacher responsibilities; (2) The Role of Principal Leadership in improving teacher professional competencies, namely by opening discussion forums at every opportunity to find solutions, involving teachers in training; and (3) Obstacles to the leadership of school principals in improving teacher professional competence, still lack of teacher awareness in improving their abilities, teachers lacking mastery of IT, not yet active part of some teachers in KKG activities, and lack of facilities and infrastructure that can support effective learning. Keywords: principal leadership style, teachers’ professional competence, Banda Aceh http://dx.doi.org/10.23960/jpp.v11.i2.202121